THE IMPACT OF APPLYING PROJECT-BASED LEARNING TECHNIQUES ON DEVELOPING CRITICAL AND ANALYTICAL THINKING SKILLS IN HISTORY - Faleeha Oleiwi Nayyef (PT. Antis International Publisher, 2026)
Objective: This study aimed to determine the impact of applying project learning techniques in developing critical and analytical thinking skills in the subject of history for middle school students. Method: The study relied on experimental curriculum, and the SPSS statistical analysis program was used to analyze data to test the health of the hypotheses. Results: The research found that there is a moral impact on the application of project learning techniques in developing critical and analytical thinking skills in history for middle -grade students in the post application. Novelty: Based on the results, the researcher presented a number of recommendations, the most prominent of which are: the need to discuss the teacher to students with the details of the project plan and its goals and clarify some of the difficulties that can face them, and to help them choose the project's work tools in order to achieve the desired benefit from the educational project, and to provide an educational environment that allows learners to discuss Their ideas and analyzes, presenting their conclusions, and giving them the freedom to criticize ideas and information in light of specific educational standards.